2017
DOI: 10.1039/c6ra26581b
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of aminoglycoside antibiotics in feeds using high performance liquid chromatography with evaporative light scattering detection

Abstract: A HPLC-ELSD method was developed for the simultaneous detection of ten aminoglycoside antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Recently, however, the Ministry of Agriculture approved 21 antibiotic products that may be added as growth promoters in commercial feeds [8]. Previous studies reported high concentrations of several antibiotics in animal commercial feeds in China [12,32]. Our study found that all farmers used commercial feeds on their farms.…”
Section: Famers' Practice Of Antibiotic Usementioning
confidence: 59%
“…Recently, however, the Ministry of Agriculture approved 21 antibiotic products that may be added as growth promoters in commercial feeds [8]. Previous studies reported high concentrations of several antibiotics in animal commercial feeds in China [12,32]. Our study found that all farmers used commercial feeds on their farms.…”
Section: Famers' Practice Of Antibiotic Usementioning
confidence: 59%
“…According to the regulation of European Union (European Commission 2010), the maximum residue limits (MRL) for kanamycin (KAN) and streptomycin/dihydrostreptomycin (STR/diSTR) in cow milk are 150 and 200 ng mL À1 , respectively. Besides conventional chromatography methods (Preu et al, 1998;Oertel et al, 2004;Kaufmann & Maden, 2005;Liu et al, 2017), immunoassays have been applied to screen the antibiotics in animal-origin food due to be sensitive, rapid and easy-operated (Verheijen et al, 2000;Abuknesha & Luk, 2005;He et al, 2016;. Besides detecting one target specifically by immunoassay (Gu et al, 2016;Kong et al, 2017), another demand to develop the multiplex assays for more targets is growing concern because of its benefits, such as enhancing sample throughput, shorting assay time and decreasing sample consumption and cost (Zhang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Aminoglycosides (AGs) are broad‐spectrum antibiotics, which are particularly active against both gram‐positive and gram‐negative bacteria . In aquaculture, AGs have been widely used as veterinary drugs to treat bacterial infectious diseases .…”
Section: Introductionmentioning
confidence: 99%
“…Aminoglycosides (AGs) are broad-spectrum antibiotics, which are particularly active against both gram-positive and gram-negative bacteria. 1 In aquaculture, AGs have been widely used as veterinary drugs to treat bacterial infectious diseases. 2 In recent years, AGs have also been employed as a feed additive to promote growth and increase feed efficiency, because it can facilitate absorption of nutrition in animals.…”
Section: Introductionmentioning
confidence: 99%